2021
DOI: 10.1016/j.tplants.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of the natural antisense transcript puzzle

Abstract: In plants, thousands of genes are associated with antisense transcription, which often produces noncoding RNAs. Although widespread, sense-antisense pairs have been implicated in a limited variety of functions in plants and are often thought to form extensive dsRNA stretches triggering gene silencing. In this opinion, we show that evidence does not support gene silencing as a major role for antisense transcription. In fact, it is more likely that antisense transcripts play diverse functions in gene regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…Moreover, there are a great number of natural antisense transcripts (NATs) in human cells which is almost equal to sense transcripts, most (>91%) of them are ncRNAs 60 . NATs were suggested to interfere with the expression of sense mRNA through gene silencing, nuclear retention, epigenetic silencing or other mechanisms 61, 62 . Further investigations are needed to reveal the independent role of NATs, especially in the process of 3D genome organization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are a great number of natural antisense transcripts (NATs) in human cells which is almost equal to sense transcripts, most (>91%) of them are ncRNAs 60 . NATs were suggested to interfere with the expression of sense mRNA through gene silencing, nuclear retention, epigenetic silencing or other mechanisms 61, 62 . Further investigations are needed to reveal the independent role of NATs, especially in the process of 3D genome organization.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that the relative expression levels of many of the MATE NATs are positively correlated to the corresponding sense transcripts ( Figure 2 ). Whether NATs promote or reduce the target transcript stability has been a subject of debate [ 25 , 44 ]. Nevertheless, there has been accumulating evidence to support the synergy brought forth by cis -NATs on the sense mRNA [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether NATs promote or reduce the target transcript stability has been a subject of debate [ 25 , 44 ]. Nevertheless, there has been accumulating evidence to support the synergy brought forth by cis -NATs on the sense mRNA [ 25 ]. In the global identification of Arabidopsis long non-coding RNAs (lncRNAs), based on the Pearson correlation coefficients, the strong tendency of NATs to positively regulate the expression of their sense overlapping genes was suggested [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these RNAs seem to have regulatory roles, positively [ 10 , 11 ] or negatively [ 12 ] regulating the expression of other genes, such as the natural antisense transcripts (NATs). NATs are transcribed in the opposite orientation and are complementary to the sense transcripts (with mismatches or perfect matching) in the same (cis-NAT) or another locus (trans-NAT) [ 13 ]. In general, cis-NATs are easily identified in transcriptome studies, and most of the well-known NATs belong to this class.…”
Section: Introductionmentioning
confidence: 99%